BLOCKCHAIN TECHNOLOGY IN CROSS-BORDER PAYMENTS: REVOLUTIONIZING GLOBAL FINANCIAL SYSTEMS - Muchamad Bachtiar; Livia Alves; Rafaela Lima (Journal Markcount Finance, 2026)
Cross-border payment systems play a critical role in global trade and financial integration, yet they remain burdened by high transaction costs, long settlement times, limited transparency, and dependence on multiple intermediaries. This study aims to examine the role of blockchain technology in revolutionizing cross-border payments and to assess its implications for global financial systems. The research focuses on identifying key efficiencies, challenges, and systemic changes introduced by blockchain-based payment solutions compared to conventional cross-border banking infrastructures. A qualitative analytical research design was employed, utilizing an integrative review of peer-reviewed literature, industry reports, and documented blockchain-based payment initiatives. The data were analyzed thematically to compare operational processes, cost structures, governance mechanisms, and risk management features of blockchain-enabled and traditional payment systems. The findings indicate that blockchain technology significantly reduces transaction costs, enhances settlement speed, and improves transparency in cross-border payments. However, challenges related to regulatory fragmentation, scalability, interoperability, and cybersecurity remain substantial barriers to large-scale adoption. The study concludes that blockchain technology has the potential to revolutionize global cross-border payments, particularly when supported by regulatory harmonization and institutional collaboration.